INFLUENCE OF ADDITION OF PAPAIN ENZYME DIFFERENTLY TO PRECIPITATES AND SUPERNATAN PROTEIN HYDROLYSATE MACKEREL FISH(Euthynnus affinis) - Bella Andita Anggreini; Rahman Karnila; Edison ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research aims to determine the addition of the good kinds papain enzyme for producing protein hydrolysate mackerel that has a value of precipitates and supernatant highest, the chemical content proximate of mackerel meat, protein hydrolysate, and amino acid total. The method used was experimental and composed as completely randomized design (CRD). The treatment were the used to generate the best proteins hydrolysate mackerel consisting of variety of different enzyme concentrations, namely: 6%, 8%, and 10%. Proteins hydrolysate mackerel were evaluated by precipitates value, supernatant highest, the proximate of mackerel meat and the proximate proteins hydrolysate mackerel level of water, ash, protein, fat and amino acid total. The results showed that the proximate of mackerel meat is water content 62,86 (%gw), ash content 7,05 (%dw), protein content 63,57 (%dw), and fat content 4,03 (%dw). The best kind of the concentration of the papain enzyme 10% because has the contents of presipitate 31,1 gr, the contents of supernatant 48,6 ml, but not significantly different from the value of the concentration of papain enzyme 8% of precipitate 31,4 gr, supernatant 47,6 ml. Thus, considering the use of 10% inadequate papain enzyme it can be replaced by papain enzyme concentration 8%. The result showed that the proximate from concentrate 10% is water content 86,91 (%gw), ash content 22,68 (%dw), protein content 45,30 (%dw), fat content 2,52 (%dw) and has 15 types of total amino acids consisting 8 types of essential amino acids and 7 types of non-essential amino acids, but not significantly different with treatment of enzyme consentration 8%.Keywords: Fish protein hydrolysate, Euthynnus affinis, Papain enzymatic